Pharmaceutical attention to the risks of inappropriate use of marijuana in the treatment of depression (Research, Society and Development, 2022)
First, it's worth noting that this study focuses on marijuana exposure as a treatment for depression. Marijuana became a social problem and was prohibited, thus restricting its use in medicine and became a plant with adjectives that marginalized its consumer in society. Thus, the objective of this study was to present marijuana as an alternative treatment for depression, and to expose how it can become a public health problem. This research is exploratory in relation to the selection of authors through the weighting of works from the years 2004 to 2019, as scientific articles that served as the basis for the research. Depression is the disease of the century, as some call it. This disease does not choose age, sex, color and gender, some have a family history, others do not, and require treatment through medication and therapies. The objective of the discipline was achieved, and the results obtained were that marijuana cannot be used as a treatment for depression, since it generates dependence. However, drugs derived from marijuana have satisfactory efficacy for this pathology and are already recommended by several authors as an alternative to medicine of natural origin for the treatment of depression. However, it is noteworthy that depressed patients need to seek medical assistance to start treatment with this type of medication, as these are restricted.